2016
DOI: 10.1590/2175-7860201667554
|View full text |Cite
|
Sign up to set email alerts
|

Flora das cangas da Serra dos Carajás, Pará, Brasil: Urticaceae

Abstract: ResumoEste estudo engloba as espécies de Urticaceae registradas nas vegetações de cangas da Serra dos Carajás, Pará, trazendo descrições detalhadas, ilustrações e comentários morfológicos das espécies. Foram encontrados cinco gêneros e sete espécies de Urticaceae para a área de estudo. Palavras-chave: Cecropieae, conservação, FLONA Carajás, taxonomia, Urticeae. AbstractThis study encompasses the species of Urticaceae registered for the cangas of Serra dos Carajás, Pará state, bringing detailed descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…The genus Cecropia represented more than 30% of the seeds retrieved from the traps under artificial perches in the CEF. This genus is typical of regenerating forest and produces soft fruit with small seeds that are very attractive to many animals (Gaglioti et al 2016). The birds that landed on the artificial perches in the CEF and defecated seeds would have fed on fruit produced in the surrounding areas of forest.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Cecropia represented more than 30% of the seeds retrieved from the traps under artificial perches in the CEF. This genus is typical of regenerating forest and produces soft fruit with small seeds that are very attractive to many animals (Gaglioti et al 2016). The birds that landed on the artificial perches in the CEF and defecated seeds would have fed on fruit produced in the surrounding areas of forest.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, seeds of the genera Cecropia and Miconia were the most abundant in the fecal samples collected. Cecropia and Miconia are pioneer plants that produce succulent fruits with minuscule seeds throughout the year (Gaglioti, Scabbia, & Romaniuc-Neto, 2016), which would likely account for the large numbers of seeds from the two genera found in the fecal samples collected during the present study. Cecropia latiloba presented the highest index of importance due to the large numbers of its seeds in the fecal samples.…”
Section: Discussionmentioning
confidence: 92%
“…Based on literature data on floral resources available from plant species, Chamaecrista type, Solanum type, Myrcia types 2 and 3, Psidium type, Brosimum type and Laporteaaestuans type are probably related to other pollen sources (Machado & Lopes, 2006;Gressler et al, 2006;Pederneiras et al, 2011;Gaglioti et al, 2016), but they were little exploited by this population of C. flavifrons in the temporal window analyzed. Although Stigmaphyllon species are exploited for pollen by Centridini bees (Sigrist & Sazima, 2004), the frequency of occurrence S. blanchetii type in our samples suggested that the related plant was exploited only by oil.…”
Section: Discussionmentioning
confidence: 99%